The Role of E-Learning in Transferring Arabic Culture to Non-Native Speakers - Al-Rawashdeh, Sukinh Yousef (Journal of Ecohumanism, 2025)
This research explores the use of e-learning to promote Arabic culture among non-speakers of Arabic in post-COVID education settings. With increased reliance on online language teaching platforms, the research looks to determine how far such materials contribute to cultural immersion or understanding. The research adheres to a qualitative analytic pattern based on an extensive literature review and examination of real practices and tools for e-learning the Arabic language and culture. The sample included e-learning courses, online tools, the feedback of the instructors, and the experience of students. The results express a radical change in the use of e-learning technologies now after the pandemic and switching attention to more interactive, culturally saturated learning environments. However, despite how much the technology has grown, cultural content is still marginalized or even absent from most digital curricula. Some of these are the lack of teachers’ training, a suitable culturally responsive curriculum, and the dominance of Modern Standard Arabic over dialectic and cultural diversity. It has also been shown that culturally interactive media such as storytelling software, virtual classrooms, and interactive video simulations are more involved with the learners and culminate in a maximum understanding of culture. The thesis argues that e-learning can effectively teach Arabic culture if the instructional design becomes meaningfully oriented to cultural goals and instructors acquire the necessary digital and intercultural competencies.